2019
DOI: 10.1115/1.4042163
|View full text |Cite
|
Sign up to set email alerts
|

Tonal Noise Prediction of a Modern Turbofan Engine With Large Upstream and Downstream Distortion

Abstract: Ultra-high bypass ratio (UHBR) engines are designed as compact as possible and are characterized by a short asymmetric air inlet and heterogeneous outlet guide vanes (OGVs). The flow close to the fan is therefore circumferentially nonuniform (or distorted) and the resulting noise might be impacted. This is studied here at take-off conditions by means of a simulation of the unsteady Reynolds-averaged Navier–Stokes (URANS) equations of a full-annulus fan stage. The model includes an asymmetric air inlet, a fan, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…A recent alternative, better suited for the identification of acoustic phenomena at particular frequencies, is the Dynamic Mode Decomposition (DMD) [31], a technique which aims to group coherent spatial features into modes of a single temporal frequency [32,33]. It has been used in recent investigations of, for instance, cavity flow [34], airfoil buffeting [35], fan [36] combustion [37,38] and landing gear [39] noise, and turbocharger acoustics [40,41], among others.…”
Section: Dynamic Mode Decompositionmentioning
confidence: 99%
“…A recent alternative, better suited for the identification of acoustic phenomena at particular frequencies, is the Dynamic Mode Decomposition (DMD) [31], a technique which aims to group coherent spatial features into modes of a single temporal frequency [32,33]. It has been used in recent investigations of, for instance, cavity flow [34], airfoil buffeting [35], fan [36] combustion [37,38] and landing gear [39] noise, and turbocharger acoustics [40,41], among others.…”
Section: Dynamic Mode Decompositionmentioning
confidence: 99%
“…Several recent studies have therefore focused on the impact of distortion on the noise emitted by turbofan engines [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…They have shown that the tone noise characteristics can be significantly modified by: (a) introducing new acoustic sources caused by the distortion/fan blades interaction [3,4,8], (b) modifying the conventional fan-blade wakes/Outlet…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is typically the case during landing or take-off operations (angle of attack around 10°-15°) where airport neighbours are the most exposed to noise nuisance. Several recent studies have therefore focused on the impact of distortion on the noise emitted by turbofan engines [1][2][3][4][5][6][7][8]. They have shown that the tone noise characteristics can be significantly modified by: (a) introducing new acoustic sources caused by the distortion/fan blades interaction [3][4][5], (b) modifying the conventional fan-blade wakes/Outlet Guide Vanes (OGVs) interaction [3][4][5]8], and (c) modifying the generation and propagation of fan-blade shocks at transonic speeds [1][2][3][5][6][7].…”
Section: Introductionmentioning
confidence: 99%